Abundance, diversity, and community awareness of crawling insects across five land use types in a semi-arid region - Naza Emanuel Mmbaga; John Asante Johnson; Happiness Jackson Nnko; Stanslaus Terengia Materu (Discover Animals)
Abstract Crawling insects play critical roles in ecosystem functioning, yet their diversity and public perception in urban African landscapes remain underexplored. This study assessed the abundance, diversity, and community awareness of crawling insects across five land-use types (dumpsites, natural vegetation, near buildings, near roads, planted vegetation) at the University of Dodoma, Tanzania. Using pitfall traps, sticky traps, and direct picking, we collected 2,345 insects, primarily Hymenoptera (81.84%, Monomorium minimum dominant, Berger-Parker d = 0.31). Dumpsites and near buildings showed the highest species richness (S = 9–12, Margalef’s d = 1.33–1.80) and diversity (Shannon H = 1.92–2.00), with Pheidole megacephala and Odontotaenius disjunctus as key indicators (IndVal > 0.70). Community awareness was high for pest species (100% for cockroaches, ants, termites) but low for beneficial roles (42% for food source, 0% for ornamental use). These findings highlight land-use impacts on insect biodiversity and gaps in public knowledge, recommending green infrastructure and educational programs for conservation in urban African landscapes.